The investigation of chlorpyrifos (Cpy) detection of PEDOT:PSS-MXene(Ti2CTX)-BSA-GO composite using P-ISFET reduction method - Megat Muhammad Ikhsan Megat Hasnan; Lim, G. P.; N. Nayan; Soon, C. F.; A. A. Abd Halim; M. K. Ahmad; S. M. Said; M. S. Mohamed Ali; I. M. Noor (Springer Verlag, 2022)
MXenes are two-dimensional materials that are attractive for applications as sensors because they possess high conductivity, super hydrophilicity and high surface area. There already exist substantial researches on the use of Ti3C2Tx based MXenes as electrochemical biosensors, but in contrast Ti2CTX based MXenes are rarely discussed due to their inherent resistance instability. However, the use of Ti2CTX based MXenes is still worth exploring as theoretical studies have shown that Ti2CTX possesses a significantly lower bandgap compared to many other MXenes structures. Herein, this study examines the use of Ti2CTX MXene structures in a P-channel ion-sensitive field-effect transistor (P-ISFET) for the detection of Chlorpyrifos (Cpy). Compositing the PEDOT:PSS thin film with delaminated Ti2CTX MXenes flakes with graphene oxide (GO) and bovine serum albumin (BSA) allows it to maintain its sheet resistance at around 100 kOhm for 3 days. Interestingly when using the composite thin film, the minimum threshold voltage required to observe Cpy electroreduction is −0.1 V. This is much lower than that when using titanium dioxide (TiO2), which is −1.5 V. Composite thin films containing Ti2CTX MXene are found to detect Cpy with higher sensitivity compared to thin films without MXene. This is because the presence of Mxene in the PEDOT:PSS composite thin films improves the surface area available for Cpy detection. This study highlights the potential of Ti2CTx MXene-BSA composite as a promising 2D material for enzyme-free CPY detection.